Evolution of Future Black Sea Fish Stocks under Changing Environmental and Climatic Conditions - Salihoglu, Baris; Arkin, Sinan S.; Akoglu, Ekin; Fach, Bettina A. (Frontiers in Marine Science, 2017)
Here we present a case study towards producing quantitative scientific advice on the application of the EU Common Fisheries Policy (CFP) in the Black Sea. We provide estimates of fishing mortality rates at levels which will lead to rebuilding and maintaining stocks above biomass levels that could produce maximum sustainable yield (MSY) under the IPCC RCP4.5 future climate scenario together with the business as usual (BAU) river discharge scenario. In this study, we have implemented a coupled, basin-scale circulation-biogeochemical model and used its output to feed a food web model to test near-future changes that may be observed in the Black Sea ecosystem under the influence of contemporary fisheries exploitation conditions. In order to test model response to changes in climate and related drivers, the future climate scenario (2015-2020) simulation was compared to the present day (2000-2014) simulation. Likewise, to test the sensitivity of the higher trophic level food web model to changes in fishing pressure, a future estimate of fishing pressure was projected based on its respective contemporary value and applied to each fish stock. Using these models, fishing mortality rates that could produce the maximum sustainable yield (FMSY) in future years 2015-2020 and ensure the long-term recovery of the predatory fish stocks of the Black Sea are predicted. Future projections suggest that all fish stock will decrease in all the regions of the Black Sea except for sprat. Anchovy is expected to show the highest decrease in biomass. Analyses on FMSY estimates show that a significant reduction in fisheries exploitation is required for the sustainable management of the Black Sea ecosystems and the related services. This study, for the first time, presents future stock size, FMSY and MSY estimates for the Black Sea for 11 fish species. FMSY values are generally lower than estimates of the scientific, technical and economic committee for fisheries (STECF), mainly because of the explicit food web interactions that the modeling system allows to be considered.